Sistem Kendali Parameter Suhu dan Nutrisi pada Aeroponik menggunakan Metode Regresi Linier - Andi Dwi Angga Prastya; Hurriyatul Fitriyah; Sabriansyah Rizqika Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Aeroponics is a method of growing without using soil but using nutrient water that is sprayed into the air for 24 hours.. To make plants thrive by reducing water use, there are 2 important factors that need to be considered, namely temperature and ppm. To control using Arduino Uno, for temperature reading system using DS18B20 and for reading ppm levels using a TDS sensor using linear regression method to obtain a prediction of the duration of the output on. The outputs used are 12v fans, 12v and 5v water pumps, and misting nozzles. The results for the temperature with a setpoint in the 300C planting room, get the regression equation y = 9259.9x - 161904 with R Square or r2 = 0.9162, for the RMSE value of 11.413 and the MAPE value of 7.8%. And for the PPM level with a set point of 1170 PPM, the regression equation is y = -1.3298x + 1608 with R Square or r2 = 0.9792, for the RMSE value of 54 and the MAPE value of 8.9%.. Then for the computational value of the simple linear regression equation, the result is 1159ms or about 1.156 seconds.